2018
DOI: 10.1007/s10493-018-0286-3
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal property of the essential oil from Lippia gracilis against Tetranychus urticae and a natural enemy, Neoseiulus californicus, under greenhouse conditions

Abstract: The essential oil from the leaves of Lippia gracilis was investigated for fumigant and residual activity against Tetranychus urticae (Acari: Tetranychidae) and Neoseiulus californicus (Acari: Phytoseiidae). The results were compared to eugenol, Ortus and Azamax, as positive controls. Gas chromatography (GC) and GC/mass spectrometry analysis enabled the identification of 28 compounds, accounting for 99.1 ± 0.6% of the essential oil. The major constituents were carvacrol (61%), p-cymene (11%) and thymol (11%). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…The fumigant action and residual contact effect of selected chemical constituents of EOs, including some of the selected compounds analysed in the present study, on T. urticae have previously been investigated. Born et al (2018) found the same susceptibility of T. urticae to terpinolene and β-pinene by fumigation and residual contact as that reported in the present study. Badawy, Abdelgaleil, Mahmoud, and Marei, (2018) found the same level of toxicity for limonene by fumigation (LC 50 = 10.35 mg/L air) and residual contact (LC 50 = 50.95 mg/L) compared to the present findings.…”
Section: Fumigant and Residual Contact Bioassaysupporting
confidence: 90%
See 1 more Smart Citation
“…The fumigant action and residual contact effect of selected chemical constituents of EOs, including some of the selected compounds analysed in the present study, on T. urticae have previously been investigated. Born et al (2018) found the same susceptibility of T. urticae to terpinolene and β-pinene by fumigation and residual contact as that reported in the present study. Badawy, Abdelgaleil, Mahmoud, and Marei, (2018) found the same level of toxicity for limonene by fumigation (LC 50 = 10.35 mg/L air) and residual contact (LC 50 = 50.95 mg/L) compared to the present findings.…”
Section: Fumigant and Residual Contact Bioassaysupporting
confidence: 90%
“…For instance, the oils from Piper aduncum (LC 50 = 7.17 μl/ml ≅ 7.00 mg/ml)(Araújo et al, 2012) and oils from the green (LC 50 = 7.44 μl/ml) and ripe (LC 50 = 7.29 μl/ml) fruits of Schinus terebinthifolius (Nascimento, Camara, & Moraes, 2012) were more toxic than the four Citrus oils investigated herein, whereas the oil from Vitex agnus-castus(Neves & Camara, 2016) was less toxic. In other studies using the same population of T. urticae, the oils from Lippia gracilis (LC 50 = 29.70 μl/ml)(Born, da Camara, de Melo, & de Moraes, 2018) and Aristolochia trilobata (LC 50 = 62.54 mg/ml) (de Melo, Camara, Silva Lima, Moraes,…”
mentioning
confidence: 94%
“…as acaricidal agent against the plantfeeding mite Tetranychus urticae Koch., showing toxicity against the eggs and adults, as well as oviposition deterrent and repellent activity. Good results (LC 50 = 0.06 mL/L air) were also obtained by Born et al [109] against the same mite species, using L. gracilis EO; the results also proved a high selectivity towards the tested mite, compared with its natural enemy, Neoseiulus californicus. Similar results were also obtained by Mahmoud et al [110] and Ribeiro et al [111].…”
Section: Application Of Eos As Acaricidal and Nematicidal Agentssupporting
confidence: 63%
“…Toxicity by residual contact of the chemical constituents found in essential oils against T. urticae has been investigated, including the same compounds analyzed in the present study, such as ρ-cymene, βcaryophyllene, β-pinene, α-pinene, 1,8-cineole, camphor, bicyclogermacrene and eugenol (Attia et al, 2012;Araújo et al, 2012;Moraes et al, 2017;de Melo et al, 2018;Hong et al, 2018;Born et al, 2018;Cao et al, 2019;Abdelgaleil et al, 2019;). However, this is the first report of the acaricidal activity against this pest of the constituents (E)-anethole, methyl eugenol, spathulenol, caryophyllene oxide, eugenyl acetate, α-phellandrene and βphellandrene.…”
Section: Discussionmentioning
confidence: 99%